Nontraditional Roles of Magnesium Ions in Modulating Sav2152: Insight from a Haloacid Dehalogenase-like Superfamily Phosphatase from Staphylococcus aureus - Bang, Jaeseok; Park, Jaehui; Lee, Sung Hee; Jang, Jinhwa; Hwang, Junwoo; Kamarov, Otabek; Park, Hae Joon; Lee, Soo Jae; Seo, Min Duk; Won, Hyung Sik; Seok, Seung Hyeon; Kim, Ji Hun (International Journal of Molecular Sciences, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) infection has rapidly spread through various routes. A genomic analysis of clinical MRSA samples revealed an unknown protein, Sav2152, predicted to be a haloacid dehalogenase (HAD)-like hydrolase, making it a potential candidate for a novel drug target. In this study, we determined the crystal structure of Sav2152, which consists of a C2-type cap domain and a core domain. The core domain contains four motifs involved in phosphatase activity that depend on the presence of Mg2+ ions. Specifically, residues D10, D12, and D233, which closely correspond to key residues in structurally homolog proteins, are responsible for binding to the metal ion and are known to play critical roles in phosphatase activity. Our findings indicate that the Mg2+ ion known to stabilize local regions surrounding it, however, paradoxically, destabilizes the local region. Through mutant screening, we identified D10 and D12 as crucial residues for metal binding and maintaining structural stability via various uncharacterized intra-protein interactions, respectively. Substituting D10 with Ala effectively prevents the interaction with Mg2+ ions. The mutation of D12 disrupts important structural associations mediated by D12, leading to a decrease in the stability of Sav2152 and an enhancement in binding affinity to Mg2+ ions. Additionally, our study revealed that D237 can replace D12 and retain phosphatase activity. In summary, our work uncovers the novel role of metal ions in HAD-like phosphatase activity.
Keywords: Bacterial Proteins; Crystallography, X-Ray; Hydrolases; Magnesium; Methicillin-Resistant Staphylococcus aureus; Models, Molecular; Phosphoric Monoester Hydrolases; Protein Binding; Staphylococcus aureus; crystal structure; function of magnesium ion; functional replacement; haloacid dehalogenase-like hydrolase; melting temperature; phosphatase; Staphylococcus aureus